The Development of Preschool Children Related to Democratic Parenting - Sukmandari, Ni Made Ari; Triana, Komang Yogi; Prihandini, Claudia Wuri (Poltekkes Kemenkes Jakarta III, 2022)
Every parent has their way of parenting. Parenting patterns affect the development of children, especially children in the golden period. The purpose of this study was to find out the correlation between democratic parenting and the development of preschool children. This study used a correlational descriptive design with a cross-sectional approach. This study was conducted over four months with a sample number of 50 respondents. The sampling technique used was purposive sampling with inclusion and exclusion criteria. Data collection used democratic parenting and developmental pre-screening questionnaires. Data were analyzed with SPSS programs on a univariate and bivariate basis using the Rho Spearman test with a significance value of 0.05. The results showed that most respondents with highly democratic parenting were 32 respondents (64%) and most respondents with appropriate developments were 36 respondents (72%). Correlation analysis of democratic parenting with children's development obtained a value of 0.0001, showing a meaningful correlation between democratic parenting and children's development. The results of this study were expected to increase understanding of democratic parenting and children's development perform innovative efforts in implementing democratic parenting through children's development, environmental influence and technological development.